KAJIAN SISTEM PERLADANGAN DI KABUPATEN BOLAANG MOGONDOW (STUDI KASUS PERLADANGAN DI KPHP WILAYAH II KABUPATEN BOLAANG MONGONDOW) - Susilaningsih ., Lasabuda; Hengki Djemie Walangitan; Nordy ., Waney (Sam Ratulangi University, 2017)
The study aimed to (1) describe the characteristics of the socio-economic, (2) describe the characteristic of ecological farming in the region KPHP unit II Bolaang Mongondow district, and (3) analyze the development strategy KPHP Unit II in the district based on empowerment Bolaang Mongondow cultivators. This research was conducted with descriptive and semi-quantitative approach. Data analysing for the development of management strategies used SWOT analysis. The primary data obtained through interviews in three (3) villages namely Pindolili, Village Pindol and Village Totabuan to 20 informants, consisting of 3 (three) the village chief, two religious leaders in the two (2) village, 2 (two) historians the formation of the village and 12 (twelve) cultivators in three (3) villages. While the secondary data obtained through statistical data and information obtained from the forestry policy forestry official website. Results of research on (1) socio-economic condition around the area KPHP unit II Bolaang Mongondow district shows that the agricultural sector is still the main source of livelihood of society. Socio-cultural conditions of communities in the study area are a heterogeneous society with different ethnic groups. They are still implement a culture or tradition that can threaten the sustainability of their livelihoods; (2) Ecological condition in the area KPHP unit II shows that the high danger of erosion due to geography land that shaped mountains with slope ranging from moderate to steep and the actions of farming and poor land management on critical land of steep hills. (3) Based on the results of the SWOT analysis for development strategy is the designation of priority and urgency, the development of nature tourism potential for increased use of environmental services, increased perception and participation of the formal integration of development and the development of food security by reforestation and forest conservation. The implementation strategy of forest management in the region KPHP unit II Bolaang Mongondow needs to be done in the form of maintenance of the water catchment area to ensure the availability of water production for the dam in the village Pindol, increasing role in the development of tourism and recreation participation of the parties primarily concerned to control encroachment and set the direction and strategy of development associated with the function of the ministry of forestry.